Pemanfaatan Rumput Laut Kappaphycus Sp. Di Kepulauan Yapen Papua Sebagai Bahan Bioplastik Dengan Penambahan Kitosan - Simamora, May Tree; Indriyani, Ervina; Runtuboi, Dirk Y.P.; Mishbach, Imam; Gabriela O.K; Fabianus Batlery (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
Indonesia produces 64 million tons of plastic waste every year and 3.2 million tons of it is thrown into the sea, so research needs to be done to create plastic that is environmentally friendly and easily decomposed (bioplastic). Alginate and carrageenan are polysaccharides produced from seaweed which have potential as materials for making bioplastics. This research aims to determine the effect of alginate and carrageenan on the quality, physical properties, mechanical properties and biodegradability of carrageenan-chitosan bioplastics with glycerol plasticizer. Carrageenan is obtained from extraction of Kappaphycus sp. who comes from the Yapen Islands, Papua Province. Making a carrageenan bioplastic solution by dissolving carrageenan flour (1; 1.5; 2; 2.5 grams) and 5 ml of glycerol in 100 ml volume of vingga distilled water then heating using a magnetic stirrer for 15 minutes at 90oC. The process of making a chitosan solution is by dissolving 2 grams of chitosan, 3 ml of glycerol, and 1 ml of glacial acetic acid in 94 ml of distilled water then heating with a magnetic stirrer for 10 minutes. The research results show that. The best concentration of carrageenan in the alginate-carrageenan composite bioplastic is 1.5 grams because it has physical and mechanical properties that meet the Japanese Industrial Standard and SNI 7188.7:2016 except for water resistance.